Выражение 3*(2x+3)+(10-3x)+5(1-2x) 0,1(2x+1)-1,3(2x-0,)+12 (2x-30)*0,4-0,1*(4x-0,,2-0,1x)

ученица999999999 ученица999999999    2   04.10.2019 11:40    0

Ответы
айс1705 айс1705  09.10.2020 19:30

Пошаговое объяснение:

3*(2x+3)+(10-3x)+5(1-2x)= 6x + 9 + 10 - 3x + 5 - 10x = -7x + 24


0,1(2x+1)-1,3(2x-0,5)-(-5x)+12= 0,2x + 0,1 - 2,6x + 0,65 + 5x + 12 = 2,6x + 12,75


(2x-30)*0,4-0,1*(4x-0,4)-(-1,2-0,1x) = 0,8x - 12 - 0,4x + 0,04 + 1,2 + 0,1x = 0,5x - 10,76

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика